How, if at All, should the Law of Trademarks Adapt to the Rise of Sensory Marketing? - Wołangiewicz, Michał (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
This paper examines the suitability of trademark law for the regulation of sensory marks. By using academic opinion and case law, it argues that the courts in the EU are too reluctant to acknowledge the registrability of some non-conventional marks given the fact they have become traditional in practice. Finally, the paper concludes that lawmakers and officers of state agencies handling intellectual property identification should recognise certain sensory marks as registrable trademarks.
Keywords: znaki towarowe; prawo; marketing sensoryczny; własność intelektualna